(untitled) (Indonesian Nursing Science Journal, 2025)
Stunting remains a major public health issue caused by chronic malnutrition, often influenced by mothers’ inadequate knowledge and attitudes regarding child care and nutrition. This study aimed to determine the effectiveness of booklet-based health education in improving mothers’ knowledge and attitudes toward stunting prevention. This research employed a pre-experimental design with a one-group pretest-posttest approach, conducted between May 15 and June 1, 2023. The population consisted of 506 mothers with children under five years in RW 09, and a total of 83 respondents were selected through purposive sampling. The results showed an average increase of 1.59 in knowledge scores and 6.9 in attitude scores after the intervention. Marginal Homogeneity and McNemar tests revealed a significant difference before and after the intervention (p-value = 0.000). This study confirms that booklet media is effective in enhancing mothers’ knowledge and attitudes regarding stunting prevention and is recommended for broader use in health education programs.